Antimicrobial Resistance: An Update from the Canadian Committee on Antibiotic Resistance - Canadian Committee on Antibiotic Resistance (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present article is one of a series prepared by the Canadian Committee on Antibiotic Resistance (CCAR). These articles are designed to update readers on current activities intended to limit the development and transmission of antibiotic resistance in Canada. Headquartered in Vancouver, British Columbia, the CCAR provides outreach to public and professional communities through activities focused on infection prevention and control, resistance surveillance and optimal antibiotic use.